BRAINLIEST!!!!
What is (f−g)(x)?
f(x)=3x^5+6x^2−5
g(x)=2x^4+7x^2−x+16
![BRAINLIESTWhat is fgxfx3x56x25gx2x47x2x16 class=](https://us-static.z-dn.net/files/dfc/36af034b99105c9a82519ac592d6f122.png)
![BRAINLIESTWhat is fgxfx3x56x25gx2x47x2x16 class=](https://us-static.z-dn.net/files/d28/1fd2e26f69be6812e439bf2a056da330.png)
Answer:
[tex]\large\boxed{1.\ (f-g)(x)=x^4-x^2-18}\\\boxed{2.\ (f-g)(x)=3x^5-2x^4-x^2+x-21}[/tex]
Step-by-step explanation:
[tex](f-g)(x)=f(x)-g(x)[/tex]
[tex]1.\\f(x)=x^4-9,\ g(x)=x^2+9\\\\(f-g)(x)=(x^4-9)-(x^2+9)=x^4-9-x^2-9=x^4-x^2-18\\\\2.\\f(x)=3x^5+6x^2-5,\ g(x)=2x^4+7x^2-x+16\\\\(f-g)(x)=(3x^5+6x^2-5)-(2x^4+7x^2-x+16)\\\\=3x^5+6x^2-5-2x^4-7x^2+x-16\qquad\text{combine like terms}\\\\=3x^5-2x^4+(6x^2-7x^2)+x+(-5-16)\\\\=3x^5-2x^4-x^2+x-21[/tex]